2020
DOI: 10.1016/j.seppur.2020.117253
|View full text |Cite
|
Sign up to set email alerts
|

CFD modelling of particle classification in mini-hydrocyclones

Abstract: This work presents validated Computational Fluid Dynamics (CFD) predictions of the effect that changes in vortex finder and spigot diameters have on the classification performance of mini-hydrocyclones. Mini-hydrocyclones (e.g. 10 mm in diameter) have been applied successfully to the separation of micron-sized particles since their bypass fraction is larger than the water recovery, which results in a high particle recovery to the underflow, as well as low water recovery. However, a larger bypass fraction can b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(7 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Several attempts have been made to devise a model capable of providing an accurate quantitative description of the operation of hydrocyclones. Empirical models have been developed earlier by Bradley and by Plitt, to be later revisited by Nageswararao et al Semiempirical models and first-principle models have been proposed among others by Neesse and Schubert, Bohnet, Braun, and Dueck et al , A review of the available models, their characteristics, and their pros and cons has been reported elsewhere. ,,, Alternatively, computational fluid dynamics has been used successfully for accurate modeling and for the development of novel hydrocyclone designs, traded off against a higher computational cost.…”
Section: Hydrocyclone Selection and Modelingmentioning
confidence: 99%
“…Several attempts have been made to devise a model capable of providing an accurate quantitative description of the operation of hydrocyclones. Empirical models have been developed earlier by Bradley and by Plitt, to be later revisited by Nageswararao et al Semiempirical models and first-principle models have been proposed among others by Neesse and Schubert, Bohnet, Braun, and Dueck et al , A review of the available models, their characteristics, and their pros and cons has been reported elsewhere. ,,, Alternatively, computational fluid dynamics has been used successfully for accurate modeling and for the development of novel hydrocyclone designs, traded off against a higher computational cost.…”
Section: Hydrocyclone Selection and Modelingmentioning
confidence: 99%
“…Based on a prior study, the turbulent kinetic energy needs to be second-order, and the Reynolds stresses need to be the first order. 59 To ensure the accuracy of the solution, the criterion for the convergence of the scaled residuals was set to 1 × 10 −5 . The particle trajectories were calculated using the discrete phase model (DPM), considering the volume fraction of the particles to be less than 10%.…”
Section: A Numerical Simulationmentioning
confidence: 99%
“…They found that this inlet structure can effectively improve the classification performance of their hydrocyclone compared to conventional tangential inlets. Vega-Garcia et al 23 has explored the influence of overflow and underflow size on classification performance of a mini-sized hydrocyclone through CFD modeling and experiments. Ye et al 24 developed a conical-section hydrocyclone and found that the combination of moderate conical length and modified cone with wider radial space near the underflow is effective in improving the classification performance for ultrafine particles.…”
Section: Introductionmentioning
confidence: 99%
“…They found that this inlet structure can effectively improve the classification performance of their hydrocyclone compared to conventional tangential inlets. Vega-Garcia et al has explored the influence of overflow and underflow size on classification performance of a mini-sized hydrocyclone through CFD modeling and experiments. Ye et al .…”
Section: Introductionmentioning
confidence: 99%